Role of pre-operative ultrasonography in assessment of technical difficulties during laparoscopic cholecystectomy requiring conversion to open procedure - Chatterjee, Debarghya; Vakil, Rakesh; Sharma, Rajeev; Mohanty, Arnab; Patras, Elisheba (International Surgery Journal, 2020)
Background: Cholecystectomy is the most common major abdominal surgery of the biliary tract and the second most common abdominal surgery performed in recent times. Today, laparoscopic cholecystectomy is the treatment of choice for symptomatic gallstones. Ultrasound is a non-invasive, painless investigation that will show stones in the gallbladder with sensitivity and specificity of more than 90%. The study aims at evaluating the accuracy of certain ultrasound parameters to predict a difficult laparoscopic cholecystectomy. Methods: Prospective observational study. The selected patients were explained about the procedures of ultrasonography and laparoscopic cholecystectomy, and about the advantages and disadvantages of laparoscopic cholecystectomy, along with the possibility of conversion to open procedure. Informed consent was taken. General particulars of patients, relevant history & findings on physical examination, laboratory investigations, ultrasonographic features and operative findings were noted in the study proforma. For data analysis, categorical variables were expressed as frequencies and percentages. Sensitivity, specificity and p values were calculated. P value<0.05 was considered to be statistically significant. Results: Significant association was found between all the independent ultrasound parameters and a difficult laparoscopic cholecystectomy. Presence of contracted gall bladder was found to be significantly associated with conversion to open cholecystectomy. Conclusions: It was found that ultrasonography can be a useful tool in predicting a difficult laparoscopic cholecystectomy.